Factors associated with prevention practices against COVID-19 in the Peruvian population: Disparities between rural and urban areas. - Fernandez-Guzman, D. (2022)
Objective To determine the factors associated with prevention practices against COVID-19 in the Peruvian population according to rural vs. urban locations. Methods Analytical cross-sectional study, secondary analysis based on a previously collected database. A sample of individuals over 18 years of age, residing in Peru and with no history of COVID-19was evaluated. Factors associated with prevention practices were evaluated using Poisson regressions with variance adjustment by region cluster and stratified by rurality. Results Of 3231 participants included, 2741 (84.8%) were from urban areas and 490 (15.2%) from rural areas. The frequency of good prevention practices against COVID-19 was 27.8% in our total sample. In urban areas the frequency of good prevention practices was 28.8% and in rural areas it was 22.5%. Factors associated with prevention practices against COVID-19 in both urban and rural areas were male sex (urban: aPR 0.64, 95%CI 0.55–0.75; rural: aPR 0.66, 95%CI 0.54–0.80) and self-considering adequately carrying out prevention practices (urban: aPR 2.48, 95%CI 2.13–2.89; rural: aPR 2.70, 95%CI 2.27–3.19). Conclusion The frequency of good prevention practices against COVID-19 was less than 30% in both urban and rural areas. There are differences in the factors associated with good preventive practice against COVID-19. Only sex and considering that preventive measures were adequately carried out were associated with good prevention practices in both areas. In view of this, prevention measures should be promoted taking into account cultural principles and considering geographical location in the face of present and future outbreaks or pandemics.